Modeling and Practical Implementation of a Broadband Double-Ridged Horn Antenna with an Operating Range More Than an Octave and a High Level of Cross-Polarization Discrimination - Viktor V. Meshcheriakov; Natalia V. Markova; Pavel D. Iurmanov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. The resolution of the problem of radio polarimetry in multiposition microwave screening systems (MMSS) with aperture synthesis requires the use of antennas with a high level of cross-polarization discrimination (XPD) in a wide spatial angle. The radio images are reconstructed in MMSS at distances commensurate with the aperture of the antenna structures. Therefore, the value of the spatial angle, at which high XPD is required, can reach 30°. This leads to a new problem of creating an antenna configuration of the X and Ku band, the application of which in MMSS will resolve the problem of constructing a radio image of depolarized microwave radiation scattered on the human body in the form of hidden dangerous objects.Aim. To develop a double-ridged receiving antenna for long-term operation in MMSS with an XPD level of 28 dB at a spatial angle of 30° and operating frequencies of 8…20 GHz.Materials and methods. The requirements for the receiving antenna in MMSS were determined. Theoretical justifications were proposed for the choice of antenna design. Aperture synthesis was used to construct microwave images in MMSS. The stages and results of modelling broadband double-ridge antennas were presented using the CST Studio software broadly applied for three-dimensional electro-magnetic field modelling. The results of modelling pyramidal and conical double-ridged antennas, as well as those in circular and elliptical waveguides, were analyzed. The designed antenna was tested in an anechoic chamber. The measurement results were compared with those obtained during simulation.Results. An elliptical double-ridged horn antenna with a VSWR of no more than 2 and cross-polarization discrimination in a spatial angle of 30° of no less than 28 dB for the frequency range that covers an octave was designed and constructed.Conclusion. The developed antenna can be used in MMSS for the purpose of detecting the effect of micro-wave radiation depolarization as hidden dangerous objects on a human body. Such characteristics of the antenna as its high XPD value in a wide spatial angle will allow the future introduction of microwave polarimetry in MMSS.